ACTUALIZATION OF RELIGIOUS MODERATION VALUES IN PONDOK PESANTREN - Ahmad Irfan Mufid; Gustin Gustin (Faculty of Da’wa and Islamic Communication, State Institute for Islamic Studies of Syaikh Abdurrahman Siddik Bangka Belitung, 2025)
Among the issues in this nation that always have the potential to cause conflict and are easily provoked is the religious issue. This study not only captures religious moderation as a normative concept or institutional policy but also examines the process of internalizing its values through classical and contemporary literature that forms the Pondok Pesantren learning curriculum. The method used in this research is the qualitative research method. The research location includes three Pondok Pesantren: Daar el-Qolam in Tangerang, Darul Arqam in Garut, and Bahrul Ulum in Tambak Beras. The data collection techniques used in this study were in-depth interviews and participant observation. The data analysis used was qualitative data analysis. Based on the research findings and discussion, it can be concluded regarding the actualization of religious moderation values in Pondok Pesantren education: values are justice, balance, simplicity, tolerance, unity and brotherhood, honesty and truth, non-discrimination, and preserving civilization thru students at Islamic boarding schools. In implementing religious moderation values, Bahrul Ulum Jombang Pondok Pesantren demonstrates a more comprehensive approach compared to the two modern Pondok Pesantren that were the research objects. In addition to implementing the values of moderation through the formal curriculum, this Pondok Pesantren also instills these values thru the study of yellow books to actualize religious moderation. Meanwhile, Darul Arqam Pondok Pesantren in Garut and Daar el-Qolam in Tangerang, implement a curriculum that balances religious and general sciences. The application of religious moderation values in both Pondok Pesantren is strengthened through various extracurricular programs. This approach allows students to develop cross-cultural communication skills and tolerance.